The Impact of Victim Demeanor on Jurors’ Perceptions of a Sexual Harassment Victim - Jenkins, Baylee D. (Violence against women, 2023)
Despite the prevalence of sexual harassment in the workplace, little research has investigated the role of victim demeanor in perceptions of sexual harassment cases. The present study varied whether the victim cried while testifying by using drawings of the victim. Participants were presented with a civil trial summary and asked to make trial-related judgments. Overall, factors representing participants’ perceptions of victim credibility and victim negative emotions were higher when the victim cried than when she did not. The factor representing victim credibility also mediated the relationship between victim demeanor and trial outcomes. Finally, cognitive networks demonstrated that victim demeanor was important to participants’ decision-making. The legal implications of the findings are discussed.